Where is the Great Barrier Reef? - Medina, Nico, 1982- (Where is (Grosset & Dunlap), 2017)
"In this Where Is? title, kids can explore the Great Barrier Reef--big enough to be seen from space but made up of billions of tiny living organisms. The Great Barrier Reef, off the coast of Australia, is the world's largest coral reef system. Stretching more than 1,400 miles, it provides a home to a wide diversity of creatures. Designated a World Heritage Site, the reef is suffering from the effects of climate change but this fascinating book shows this spectacular part of our planet."--